"I Find Myself Isolated and Alone": Black Women's Experiences of Microaggressions at an Hispanic-Serving Institution. Issue 2 (4th May 2019) - Willis, Tasha Y.; Mattheis, Allison; Dotson, Briauna; Brannon, Lauri-Jo; Hunter, Morgan; Moore, Autumn; Ahmed, Lina; Williams-Vallarta, Lenamarie
Abstract : This article explores the experiences of Black women students attending an Hispanic serving institution (HSI) in a large urban area with a disproportionately low number of Black students. A narrative inquiry approach was used to engage six students in reflection and discussion addressing the following research question: How does race impact the experiences of Black women studying at an HSI? Guided by a conceptual framework drawn from intersectionality theory and microaggressions, analysis revealed themes of (a) feeling "only and othered, " (b) feeling boxed in and silenced, and (c) finding support. Implications for practice in higher education are offered.